2021
DOI: 10.1136/bmjopen-2020-041645
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and experiences of self-harm and suicide in low-income and middle-income countries: protocol for a systematic review

Abstract: IntroductionOver 800 000 people die due to suicide each year and suicide presents a huge psychological, economic and social burden for individuals, communities and countries as a whole. Low-income and middle-income countries (LMICs) are disproportionately affected by suicide. The strongest risk factor for suicide is a previous suicide attempt, and other types of self-harm have been found to be robust predictors of suicidal behaviour. An approach that brings together multiple sectors, including education, labou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The latest report revealed that the age-standardized suicide rate was 6.7 per 100,000 people in 2019 globally [ 2 ]. Suicide not only brings a mental blow to the family but also causes a certain burden of disease and a negative impact on society [ 3 , 4 , 5 ]. In rural areas, the suicide rate was found to be higher than in urban neighborhoods in many countries around the world [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latest report revealed that the age-standardized suicide rate was 6.7 per 100,000 people in 2019 globally [ 2 ]. Suicide not only brings a mental blow to the family but also causes a certain burden of disease and a negative impact on society [ 3 , 4 , 5 ]. In rural areas, the suicide rate was found to be higher than in urban neighborhoods in many countries around the world [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%